Control of laser absorbing efficiency and proton quality by a specific double target. (4th August 2016) - Yu, Q; Gu, Y J; Li, X F; Qu, J F; Kong, Q; Kawata, S
Abstract: The micro-structured double-layer target is an efficient method to improve proton quality. However, the laser absorption efficiency is low due to strong reflection at the front surface of such targets. Moreover, the proton charge is limited by the driving laser radius. To overcome these shortcomings, a specific double-layer (SDL) target with a vacuum gap in the center of the heavy ion layer is proposed in this paper. In this specified target, the laser reflection effect is significantly weakened and the absorption and penetration efficiencies are greatly enhanced. The high-energy electrons from Breakout afterburner regime efficiently transfer their energy to the protons. Both the energy of the spectral peaks and maximum proton energy are greatly increased. The periodic structure of the longitudinal electric field makes the force applied on the protons becomes homogeneous in time average and therefore reduce the energy spread. In these SDL targets, the proton layer radius and the accelerated proton charge are not limited by the laser radius. With a larger-radius proton layer, the protons can be accelerated to high energy with small energy spread. When the proton layer radius is reduced to the laser radius, the SDL target is still an effective structure to improve the proton quality. The mechanism is proved by a series of particle-in-cell simulations.